If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (17 + 2w)(13 + 2w) = 396 Multiply (17 + 2w) * (13 + 2w) (17(13 + 2w) + 2w * (13 + 2w)) = 396 ((13 * 17 + 2w * 17) + 2w * (13 + 2w)) = 396 ((221 + 34w) + 2w * (13 + 2w)) = 396 (221 + 34w + (13 * 2w + 2w * 2w)) = 396 (221 + 34w + (26w + 4w2)) = 396 Combine like terms: 34w + 26w = 60w (221 + 60w + 4w2) = 396 Solving 221 + 60w + 4w2 = 396 Solving for variable 'w'. Reorder the terms: 221 + -396 + 60w + 4w2 = 396 + -396 Combine like terms: 221 + -396 = -175 -175 + 60w + 4w2 = 396 + -396 Combine like terms: 396 + -396 = 0 -175 + 60w + 4w2 = 0 Factor a trinomial. (-35 + -2w)(5 + -2w) = 0Subproblem 1
Set the factor '(-35 + -2w)' equal to zero and attempt to solve: Simplifying -35 + -2w = 0 Solving -35 + -2w = 0 Move all terms containing w to the left, all other terms to the right. Add '35' to each side of the equation. -35 + 35 + -2w = 0 + 35 Combine like terms: -35 + 35 = 0 0 + -2w = 0 + 35 -2w = 0 + 35 Combine like terms: 0 + 35 = 35 -2w = 35 Divide each side by '-2'. w = -17.5 Simplifying w = -17.5Subproblem 2
Set the factor '(5 + -2w)' equal to zero and attempt to solve: Simplifying 5 + -2w = 0 Solving 5 + -2w = 0 Move all terms containing w to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -2w = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -2w = 0 + -5 -2w = 0 + -5 Combine like terms: 0 + -5 = -5 -2w = -5 Divide each side by '-2'. w = 2.5 Simplifying w = 2.5Solution
w = {-17.5, 2.5}
| 2(2x-2)-3(3x+3)=-5 | | X-6y=11fory | | 93/8-62/4 | | f(x)-g(x)=0 | | 2(x+1)-3(x-2)=5-(x-1) | | 3/8/2/9 | | 4(x+3)=9x-7 | | 10x^2+105x+360=0 | | 4(x+3)=9x+7 | | 8-4x=13+x | | 3(x+7)=5x-9solve | | 18n^2-50=0 | | (3x-8)(-5)-(4-x)= | | 3(x+7)=5x-9 | | (-5/(2v-6))+4=6/(v-3) | | (2+3x)+62=90 | | (2+3x)+62=360 | | (2+3x)+62=180 | | 3(x+1)-2(x-1)=9 | | 5/3-1/6 | | x/7=47 | | x/-3=46 | | (x-24)+29+296=360 | | 4(2x-1)=2(3x-2) | | (3a/4)+5=(5a/6)+2 | | 3a/4+5=5a/6+2 | | (3x+18)93=180 | | (x+1)(x+11)=-14 | | 9+4lnx=14 | | w-4=3 | | (x^2-9)/(x+4)(x+3)=0 | | (2n+6)/3=((9n-4)/5)-n |